2018
DOI: 10.1007/s40430-018-1382-3
|View full text |Cite
|
Sign up to set email alerts
|

A combined numerical and experimental study on metal expansion bellows for STHE

Abstract: Bellows is the pliable component of an expansion joint comprises one or more convolutions and the end tangents. The numbers of convolutions in a bellows are in direct connection to the extent of thermal or mechanical crusade in the piping system or heat exchanger. Metal bellows compressed under pressure and protracted under void. The bellows returns to its usual shape as the pressure or vacuum release. The aim of this paper is to design and investigate the performance of the metal expansion bellows as per the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In U-convolution bellows, maximum membrane stresses are lower than the pressure base bending stresses except for the deep, convoluted bellows and thin-walled bellows. Tangent stresses and circumferential membrane stresses also prove insignificant in the design process and have shallow values, even compared with membrane stresses [29][30][31]. Bellows are such a unique, flexible mechanical component, in which independent parameters governing the expansion-contraction process can be controlled only at the design stage.…”
Section: Location Of Tangential Membrane Stress (S 1 )mentioning
confidence: 99%
“…In U-convolution bellows, maximum membrane stresses are lower than the pressure base bending stresses except for the deep, convoluted bellows and thin-walled bellows. Tangent stresses and circumferential membrane stresses also prove insignificant in the design process and have shallow values, even compared with membrane stresses [29][30][31]. Bellows are such a unique, flexible mechanical component, in which independent parameters governing the expansion-contraction process can be controlled only at the design stage.…”
Section: Location Of Tangential Membrane Stress (S 1 )mentioning
confidence: 99%
“…Chen and Ozaki [14] investigated the circumferential strain concentrations in cylindrical and square tubes with corrugated surface subjected to axial compression using the finite element method. And Gawande [15] developed a combined numerical and experimental study on metal expansion corrugated tube for STHE. These literatures indicated that it is conducive to predicting to predict energy absorption capacity of the tubes introduced the corrugation.…”
Section: Introductionmentioning
confidence: 99%
“…An expansion joint is a connector that can expand under different forms of loading while remaining structurally sound [1][2][3]. It is composed of bellows and other components and can compensate for thermal and mechanical deformations, absorb mechanical vibrations, reduce stress, and increase the average service lives of pipes and tubes.…”
Section: Introductionmentioning
confidence: 99%